Histopathological spectrum of ovarian tumors in Jharkhand, India: A retrospective study - Manoj K. Paswan; Helen M. M. Tudu; Smita Kumari Gupta; Saurav Banerjee; Deepali Tirkey (Journal of Family Medicine and Primary Care)
Background: Ovarian tumors are the most prevalent neoplasms worldwide, affecting women of all ages. According to Globocan’s 2022 projections, by 2050, the number of women diagnosed with ovarian cancer worldwide will increase by over 55% to 503,448. The number of women dying from ovarian cancer is projected to increase to 350,956 each year, an increase of almost 70% from 2022. Aims and Objectives: The aim of this study was to analyze the various histopathological spectra of ovarian tumors according to the latest 2020 WHO classification and to assess the age distribution, frequency of incidence, and laterality of different subtypes of ovarian tumors. Materials and Methods: This retrospective study included 190 cases of histopathologically proven ovarian tumors reported by the pathology department from March 2020 to March 2024 at the Rajendra Institute of Medical Sciences, Ranchi, Jharkhand, India. Results: A total of 190 cases were studied, 154 (81.1%) were benign, 8 (4.2%) were borderline, and 28 (14.7%) cases were malignant. Surface epithelial tumors (SETs) were the most common (n = 139, 73.2%), followed by germ cell tumors (GCTs) (n = 38, 20%). Serous cystadenomas (n = 63, 33%) were the most common benign tumors, whereas the most common malignant tumors were serous carcinomas ( n=11, 5.7% ). Most ovarian tumors (n = 45, 23.68%) occurred in the 31–40-year-old age group. Conclusion: The present study showed various histopathological patterns of ovarian tumors. This study indicated a slight increase in the prevalence of malignant ovarian tumors in the middle-aged group and and a relative increase in the percentage of SETs over GCTs in recent years in our tertiary care center in Jharkhand, India. With limited resources in our institute, histopathological examination remains the mainstay for the early diagnosis of these tumors and their timlely and appropriate management. Categories: Pathology.